ANALYSIS OF STOCK PRICE EVALUATION IN THE ENERGY SECTOR AND CONSUMER CYCLICAL SECTOR DURING IPO AND AT THE END OF 2024 - Prasetya, Fikri Dwi; Sri Suryaningsum (CV. Fahr Publishing, 2024)
This study aims to evaluate the performance of energy and consumer cyclical sector stocks on the Indonesia Stock Exchange by comparing the stock price at the end of 2024 to the share price at the time of the Initial Public Offering (IPO) as the basis for an investment strategy in 2025. This study uses a quantitative method with differential test analysis, with data from 21 companies in the energy sector and 49 companies in the consumer cyclical sector that meet the sample criteria. The study results show that in hypothesis 1, there is no significant difference between the share price at the time of the IPO and the end of 2024 in energy sector companies. For hypothesis 2, there is a significant difference between the share price at the time of the IPO and the end of 2024 in companies in the consumer cyclical sector. For hypothesis 3, there is no significant difference in stock prices during IPOs between the energy sector and consumer cyclical, with the average stock price at the time of IPO in the energy sector higher than that of the consumer cyclical sector. For the 4th hypothesis, there is a significant difference in stock prices at the end of 2024 between the energy and consumer cyclical sectors, with the average stock price at the end of 2024 in the energy sector being higher than in the consumer cyclical sector.